DIGITALISASI SERTIFIKAT TANAH MELALUI PROGRAM ELEKTRONIK BADAN PERTANAHAN NASIONAL: TANTANGAN DAN KEPASTIAN HUKUM DALAM SISTEM AGRARIA INDONESIA - Agustinus Luturmas; Odilo Dwi Suharto Fautngilyanan (Fakultas Hukum, Universitas Caritas Indonesia, 2026)
Advancements in information technology have prompted the Indonesian government to undertake a digital transformation across various public service sectors—including land administration—through the implementation of electronic land certificates. This policy is part of an effort to modernize land administration to enhance service efficiency, strengthen legal certainty, and minimize issues prevalent in conventional land systems, such as document forgery, duplicate certificates, and